Analisis Dampak Sistem Digitalisasi pada Perusahaan Terhadap Efektivitas dan Efisiensi Kinerja Karyawan di Wilayah Tegal - Mawarti Mawarti (Pusat Riset dan Inovasi Nasional, 2026)
In the era of rapid technological advancement, digital transformation has become an essential strategy for companies in improving operational performance and organizational competitiveness. Various business systems are now automated and digitized to support more effective and efficient work processes across different sectors. This study aims to analyze the impact of implementing a digitalization system on employee performance effectiveness and efficiency within a company. The research employed a qualitative method using a case study approach, while data were collected through interviews with employees involved in the digital system implementation process. The findings reveal that the implementation of digital systems significantly improves employee performance by accelerating work processes, reducing manual errors, and enhancing communication and data accessibility. Nevertheless, several challenges remain, including unstable internet connections, system bugs and errors, and the continuous need for software updates, which may temporarily disrupt employee productivity and workflow. Therefore, proper technological support and system maintenance are crucial for maximizing digitalization benefits.